Perspectives on Research - 1980. (Book Review). - Meyer, Philip E.; Corbin, Donald A. (The Accounting Review, 1981)
Abstract Reviews the book "Perspectives on Research–1980 Beyer Consortium," edited by Raghavan D. Nair and Thomas H. Williams.